Farelo integral de arroz parboilizado na alimentação de codornas japonesas (Coturnix coturnix japonica) nas fases de crescimento e produção - Quevedo Filho, Ivan Bezerra (2012)
This study aimed to evaluate the inclusion of parboiled rice bran (PRWB) in diets of Japanese quail in the growing and production. In the first experiment, we used 324 Japanese quails with seven days of age, distributed in a completely randomized design with six treatments and six replications of nine birds. Treatments consisted of six diets isonutritives, being a control diet without PRWB and the other containing 5, 10, 15, 20 and 25% of PRWB. The diets were offered ad libitum within 7 to 42 days and at the end of the growth phase the birds were transferred to the production hall being fed the same ration posture for 63 days. In the growth phase, the inclusion of PRWB above 5% linearly reduced digestibility of dry matter and gross energy of the feed, and from 14.27% in nitrogen digestibility, having, however, a linear increase in metabolizing energy. Feed intake, weight gain and final weight reduced without changing the feed conversion and body composition. During production, the addition of PRWB in the diet increased the growth of age at first egg production without influence (p <0.05) age to reach 50% yield, laying percentage, feed intake, weight and egg mass and feed conversion. Although there was some reduction of parameters when the PRWB increased above 5%, there was no deterioration in performance of birds fed different levels of PRWB in relation to the control group. Furthermore, the use of up to 25% PRWB provided the best economic feasibility. In the second experiment, a total of 448 quails at 17 weeks of age were randomly allotted in a completely randomized design with seven treatments and eight replicates of eight birds. We tested a control diet (without PRWB) and six diets containing 5, 10, 15, 20, 25 and 30% PRWB. Rising levels of PRWB not influence the digestibility of nutrients, harnessing the energy of the diets, consumption, production, weight, and egg mass indices and economic feasibility. As for the quality of the eggs, we observed a linear decrease in the percentage of egg specific gravity and yolk color, with increasing inclusion of PRWB, while the percentage of yolk, albumen and Haugh units were not affected significantly. Whereas the utilization of nutrients in the ration and the performance of birds fed 30% inclusion of PRWB was not significantly lower than that obtained for the control group, while the quality of the shell, although they differ significantly from the results obtained with control diet are - within the average values reported. Thus, we can recommend the inclusion of parboiled rice bran in diets for Japanese quail at levels up to 25% in the growth phase and 30% in the production phase.